Exploring The Dynamics of Customer Loyalty: A Case Study on The Green Rapid Test Brand Investigating The Roles Of Service Quality, Product Quality, and Promotion with Customer Satisfaction As An Intervening Variable - Yusuf Suhardi; Antaiwan Bowo Pranogyo; Ahmad Afif (Return : Study of Management, Economic and Bussines, 2024)
This study aims to evaluate the impact of service quality, product quality, and promotion on customer loyalty, with customer satisfaction as a mediator, on consumers of green brand rapid test products in 10 hospitals in Bekasi City. Involving 74 respondents, this study uses a quantitative approach and associative strategy, with data collected through purpose sampling techniques and analyzed using the SmartPLS 3.0 application. The results showed that service quality and product quality had no significant effect on customer satisfaction, while promotion had a significant positive impact. Although promotion positively affects customer loyalty, service quality and product quality have no significant impact on customer loyalty. Furthermore, customer satisfaction does not significantly mediate the relationship between these factors and customer loyalty. These findings provide important insights for companies in developing more effective marketing strategies to increase customer loyalty for green brand rapid test products.